PENERAPAN MODEL PEMBELAJARAN BERDASARKAN MASALAH (PBM) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SDN 187 PEKANBARU - Melda Khalidaziah Yusbar; Lazim Lazim; Muhammad Fendrik (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The problem in this research is low the students’ IPS score learning of V grade SDN 187 Pekanbaru, with an average score of daily tests is 63,38 and it is is under the standard of KKM that defined by school had score 75. To overcome that problem, one of the learning models that can increase the IPS score is problem based learning model. The subject in this research is students of V grade SDN 187 Pekanbaru that totally 40 students. The formulation of the problem in this research: What does the implementation of problem based learning model can increase the students’ IPS score learning of V grade SDN 187 Pekanbaru? The type of this research is classroom action research used 2 cycles. This research held on March until April 2018. The result of this research presents the teacher’s activity in learning process during implementation problem based learning on the cycle I first meeting 65% and on cyle II second meeting increase became 95%. The students’ activity on cycle I first meeting 55% and on cyle II second increase became 95%. Students’ score learning increased, there is average of daily test on based score before implementation of problem based learning model is 63,38, and then on cycle I average the students’ score is 75,38 with percentage 18,93%. Then on cyle II increasing again became 81,25 with percentage 28,19% from based score. The mastery of student learning score on cyle I is 27(67,50%) students that pass. On cycle II there is 35(87,50%) students that pass. Based on this research result it can be concluded that implementation of problem based learning model can increase the students’ IPS score learning of V grade SDN 187 Pekanbaru.Keywords : Problem Based Learning Model, IPS, V grade SDN 187 Pekanbaru